2004
DOI: 10.1089/109264104773513106
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Appendectomy with Appendix Mass in Children

Abstract: Laparotomy for complicated appendicitis with a mass has been the traditional approach in the presence of acute lower abdominal pain, generalized peritonitis, and fever. Generous right iliac fossa incisions are routinely done to deal with these cases, as the appendectomy can be difficult due to visceral adhesion, omental wrapping, and early abscess formation within the mass. Laparoscopic appendectomy can result in decreased pain due to smaller wounds, as well as providing superior cosmesis.In a two-year study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The use of laparoscopic appendectomy for cases of perforated appendicitis has been hotly debated, with some investigators citing higher rates of complications while others have found no increase in complications. [12][13][14][15][16][17][18] Our results did not support an association between method of operation and the development of a postoperative abscess.…”
Section: Commentmentioning
confidence: 60%
“…The use of laparoscopic appendectomy for cases of perforated appendicitis has been hotly debated, with some investigators citing higher rates of complications while others have found no increase in complications. [12][13][14][15][16][17][18] Our results did not support an association between method of operation and the development of a postoperative abscess.…”
Section: Commentmentioning
confidence: 60%
“…16 However, evidence supporting LA in cases with AM is limited. Its use is rarely mentioned in the literature, and we could find only 2 other reports, 8,17 both of which concluded that LA was feasible and safe, obviating the need for a second admission (interval appendectomy), and that it is beneficial for preventing misdiagnosis. On the contrary, Lee and Yin 18 suggested that the presence of an AM is a contraindication for LA.…”
Section: Discussionmentioning
confidence: 94%
“…The conversion rate in our series was kept to a minimum by adopting a new technique in difficult situations, that is, submucosal appendectomy [ 16 ]. Our policy with appendix mass was to proceed with primary intervention using laparoscopy and we did not face much difficulty during operation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%